Mammal hair in nests of four cavity-nesting songbirds: occurrence, diversity and seasonality. Issue 2 (2nd April 2016) - Harničárová, Kateřina; Adamík, Peter
ABSTRACT: Capsule: The diversity of mammal hair found in nest linings varied between bird species and with season. Aims: We examined mammal species composition in the guard hair material of four cavity-nesting songbirds, focusing on their numbers and occurrence, nest predation and seasonality. Methods: We surveyed 219 nests of four cavity-nesting songbirds breeding in a Central European woodland and identified hairs from 28 mammal species. Results: Roe Deer Capreolus capreolus hair was the most commonly used hair type in the nests of all four songbird species. This was especially the case in Blue Tit Cyanistes caeruleus nests, which may suggest a preference for Roe Deer hair. The greatest diversity of hairs was found in the nests of Great Tits Parus major, while the lowest was found in the Collared Flycatcher Ficedula albicollis . In flycatchers, 59% of females used only plant material for nest construction. Interestingly, we found a strong seasonal effect in hair use. Flycatcher nests that were initiated early in the season were more likely to contain mammal hair than those initiated later in the season. Similar, albeit weaker, negative seasonal effect was detected in Great and Blue Tit nests. There were no significant effects of any potential anti-predatory functions of mammalian hair in nests. Conclusion: Our study showed a clear prevalence of Roe Deer in the hair material of all bird species and certain preferences of birds for particular mammal species. When the aim is to detect a wide range of mammal species, for example, during biodiversity surveys, we advise to consider sampling effort and to focus on early breeding birds.